Research libraries in a modern environment. Issue 2 (2014) - ,
Abstract : Purpose – The purpose of this paper is to examine the monographic literature related to developments in research libraries within recent years and the strategies that they are adopting to deal with change. The main aim is to identify any visibly established directions along which research libraries adapt to their social and organizational environments.Design/methodology/approach – Qualitative content analysis was applied to identify topics emerging from the texts. The chosen texts were read and topics signifying directions of change in the immediate environment of research libraries were mapped. This initial topic map was used for ascertaining the reactions of research libraries to identified changes. The activities of libraries directed to future anticipated changes were noted separately.Findings – The review shows the surprising resilience of research libraries and their ability to change within a short period of time. This ability signifies that research and academic libraries as organizations perfectly adapt to the incessant transformations of current times, contrary to the widely spread stereotypical image of them as conservative institutions. At the same time, they seem to be keeping true to their core of mediating services to researchers and to their place in the chain of scholarly communication.Originality/value – The article identifies the main directions of transformation of research libraries and outlines their potential roles in the future of digital scholarly communication. Acknowledgements : The author is grateful to Prof. Tom Wilson who together with Frances Hultgren supported the writing of this article and who also helped to edit it.